Urbanization, inequality and property prices : equilibrium pricing and transaction in the Chinese housing market - Ge, Teng; Wu, Tao (China economic review, 2017)
The particularly overheated Chinese housing market, with its soaring property prices, has attracted a large amount of research. We point out three of its striking empirical features, which current literature leaves unexplored: co-existence of steady growth of real transaction price and excess supply, accelerations in price-to-income ratio, and significantly strong positive correlation between real transaction prices and income inequality. A search-equilibrium model is built to explain these facts. Heterogeneous buyers and homogeneous sellers randomly search for partners to trade in a frictional property market. The search equilibrium of the property market is either a high-price-and-low-transaction elitist matching equilibrium, or a low-price-and-high-transaction pooled matching equilibrium. The terms of trade determine which equilibrium arises. Empirical observations argue for the development of China's property market through evolution from a pooled matching equilibrium to an elitist matching equilibrium. We set out to show that the market equilibrium is always inefficient, due to crowding out externalities and market incompleteness. Policy experiments support redistributive tax, as a means to improve social welfare.
Keywords: Housing market; Search and match; Inequality; Optimal pricing